Analisis Implementasi Manajemen Mutu Iso 9001:2015 Pada Kegiatan Pendayagunaan Di LAZ BMH Kalimantan Timur - Rofiq, Muhamamad; Pakkana, Mukhaer (Jurnal Ilmiah Ekonomi Islam, 2023)
This research has the purpose of analyzing the application of ISO 9001:2015 quality management principles to the Utilization division at LAZNAS Baitul Maal Hidayatullah (BMH) east Kalimantan. The method in this research is descriptive qualitative using primary data and supported by secondary data. Techniques for collecting data used in this study are interviews observations of leadership and management elements, program and utilization departments as customers in this case as beneficiaries, that it is supported by notes or documents institution. While the population includes the BMH network in 4 districts/cities in East Kalimantan. Based on the results of the study, it was found that 7 ( seven ) ISO principles had been applied in the East Kalimantan BMH program and utilization division, including customer focus, leadership, people involvement, process approach, improvement, evidence-based decision-making, and good relationship management. The problems found are the understanding of amil or employees that is not optimal and consistency in a recording. The benefits of this research are expected to provide input and feedback on the implementation of ISO 9001:2015 quality management at BMH East Kalimantan.